Hydrogen production by natural gas steam reforming honeycomb ceramic catalyst, preparation method and application

CN122912863APending Publication Date: 2026-10-16BENGBU AOFU HYDROGEN ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610888449.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-08-20
Filing Date
2026-06-18
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

首先,粉末或颗粒状催化剂在反应器内易因重力或气流作用发生团聚、沉降,导致活性组分分布不均,局部过热或“冷点”现象频发,降低反应效率并加剧催化剂烧结失活

Benefits of technology

(1)本发明的天然气水重整制氢蜂窝陶瓷催化剂,采用超高孔密度蜂窝陶瓷载体,使该催化剂具有高的催化活性,蜂窝结构能够有效降低气体扩散阻力;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912863A_ABST
    Figure CN122912863A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of solid oxide fuel cell, in particular to a natural gas water reforming hydrogen honeycomb ceramic catalyst, a preparation method and an application. The catalyst comprises an ultrahigh pore density honeycomb ceramic carrier and a composite active catalytic layer coated on the pore wall of the ultrahigh pore density honeycomb ceramic carrier, the ultrahigh pore density honeycomb ceramic carrier has a mesh number of 10000-40000 meshes, and the composite active catalytic layer comprises a metal active component, modified alumina and cerium-zirconium oxide. The catalyst has high catalytic activity by using the ultrahigh pore density honeycomb ceramic carrier, the utilization rate of the active component is improved by the porous structure of the coating layer, the natural gas water reforming hydrogen reaction can be quickly started, the hydrogen production efficiency is improved, and the methane conversion rate is more than 75% at 650 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

This application claims priority to application number 2025111669703, application date: August 20, 2025, invention title "Natural Gas Water Reforming Hydrogen Production Honeycomb Ceramic Catalyst, Preparation Method and Application". Technical Field

[0001] This invention relates to the field of solid oxide fuel cell technology, and more specifically, to a honeycomb ceramic catalyst for hydrogen production from natural gas water reforming, its preparation method, and its application. Background Technology

[0002] Solid oxide fuel cells (SOFCs) are considered one of the most promising energy conversion technologies in distributed power generation, transportation, and portable power sources due to their high energy conversion efficiency, strong fuel adaptability, and low emissions. However, the stable operation of SOFC stacks is highly dependent on a continuous and efficient supply of hydrogen from the upstream hydrogen source. Therefore, developing efficient and lightweight hydrogen production components has become one of the key bottlenecks restricting the commercialization of SOFC systems. Currently, using natural gas (mainly methane) as fuel to produce hydrogen-rich syngas through reforming reactions (including steam reforming, partial oxidative reforming, and autothermal reforming) remains the mainstream technology route compatible with SOFC systems.

[0003] In natural gas reforming for hydrogen production, the performance of the catalyst directly determines the hydrogen yield, system energy efficiency, and long-term stability. Current technologies generally employ traditional reforming catalysts in powder or granular form (such as Ni / Al2O3, Ru / CeO2, etc.). While these catalysts have mature preparation processes, they exhibit the following inherent drawbacks in practical applications: First, powdered or granular catalysts are prone to agglomeration and sedimentation in the reactor due to gravity or airflow, resulting in uneven distribution of active components, frequent local overheating or "cold spots", reduced reaction efficiency and aggravated catalyst sintering and deactivation.

[0004] Secondly, the pore structure formed by particle accumulation is highly tortuous, and natural gas and reactants such as steam / oxygen need to go through long diffusion paths to reach the active sites. At the same time, the reverse diffusion of products (such as H2 and CO) is restricted, resulting in sluggish reaction kinetics, especially with a sharp drop in efficiency under high space velocity conditions.

[0005] In addition, the low thermal conductivity of the granular bed (usually less than 1 W / (m·K)) makes it difficult to achieve rapid heat transfer and temperature homogenization, resulting in insufficient catalyst utilization (usually less than 30%), which needs to be compensated by increasing the catalyst loading, thereby increasing the system volume and weight.

[0006] Finally, traditional catalysts require a separate reforming reactor (such as a fixed-bed tubular reactor), whose rigid structure is difficult to match the modular and compact design requirements of SOFC stacks; residual methane or hydrocarbons in the reformed gas are prone to carbon deposition at the SOFC anode, and particulate catalysts cannot control the gas composition in situ, requiring additional purification units, which further increases the complexity of the system.

[0007] Particulate catalysts are prone to pulverization and breakage under long-term thermal cycling or vibration conditions (such as vehicle-mounted SOFC systems). The resulting fine powder may block gas passages or contaminate the fuel cell stack, leading to performance degradation or even safety accidents.

[0008] In summary, the limitations of traditional powdered / particulate catalysts in terms of mass transfer, heat transfer, mechanical stability, and system integration have become core obstacles restricting the development of natural gas-SOFC co-processing systems towards higher efficiency, lighter weight, and longer lifespan. Therefore, there is an urgent need to develop a novel reforming hydrogen production component that combines high catalytic activity, low mass transfer resistance, excellent thermal / mechanical stability, and seamless integration into SOFCs to overcome existing technological bottlenecks. Summary of the Invention

[0009] The technical problem to be solved by the present invention is to provide a honeycomb ceramic catalyst for hydrogen production from natural gas water reforming, its preparation method and its application.

[0010] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: This invention provides a honeycomb ceramic catalyst for hydrogen production from natural gas water reforming, comprising an ultra-high porosity honeycomb ceramic support and a composite active catalyst layer coated on the pore walls of the ultra-high porosity honeycomb ceramic support. The ultra-high porosity honeycomb ceramic support has a mesh size of 10,000-40,000 mesh, and the composite active catalyst layer comprises a metal active component, modified alumina, and cerium zirconium oxide.

[0011] Furthermore, the active metallic component is nickel.

[0012] This invention also provides a method for preparing a honeycomb ceramic catalyst for hydrogen production from natural gas water reforming as described above, comprising the following steps: S1. Prepare the honeycomb ceramic carrier raw material into the ultra-high porosity honeycomb ceramic carrier; S2. Prepare the catalyst slurry for the composite active catalyst layer; S3. The catalyst slurry is coated onto the pore walls of the ultra-high porosity honeycomb ceramic carrier using a top-feed vacuum coating method. S4. Dry and calcine to obtain the honeycomb ceramic catalyst.

[0013] Furthermore, the raw materials of the cellular ceramic carrier include inorganic solid components, organic components, and water. The inorganic solid components include kaolin, spherical alumina, and talc, and the organic components include methylcellulose, polyethyleneimine, and molding release agent.

[0014] Furthermore, in the inorganic solid component, the mass percentage of kaolin is 17%, the mass percentage of spherical alumina is 65%, and the mass percentage of talc is 42%; the average particle size of the spherical alumina is less than 1 μm.

[0015] Furthermore, based on the mass of inorganic solid raw materials as 100%, the mass fraction of methylcellulose is 3-6%, the mass fraction of polyethyleneimine is 0.25-0.75%, and the mass fraction of molding release agent is 1-3%.

[0016] Furthermore, in step S2, the catalyst slurry is prepared by dissolving nickel nitrate in water, then adding modified alumina and cerium-zirconium composite, and mixing them evenly to obtain the catalyst slurry.

[0017] Furthermore, in the catalyst slurry, the mass percentage of nickel nitrate is 25%; the mass percentage of modified alumina is 65%; and the mass percentage of cerium-zirconium composite is 10%.

[0018] Further, in step S3, the upper feeding vacuum coating method involves spraying the catalyst slurry onto one end face of the ultra-high porosity honeycomb ceramic carrier, and then suctioning it from the other end face of the ultra-high porosity honeycomb ceramic carrier using compressed air at a pressure of -0.03 to -0.05 MPa.

[0019] This invention also provides the application of the aforementioned honeycomb ceramic catalyst in the hydrogen production reaction of natural gas-water reforming in SOFCs, at a temperature of 650°C and a space velocity of 5000-20000 h⁻¹. -1 Under operating conditions with a water-to-carbon ratio of 3, the aforementioned honeycomb ceramic catalyst is used to catalyze the mixture of natural gas and water.

[0020] The beneficial effects of this invention are as follows: (1) The natural gas water reforming hydrogen production honeycomb ceramic catalyst of the present invention uses an ultra-high pore density honeycomb ceramic support, which makes the catalyst have high catalytic activity and the honeycomb structure can effectively reduce gas diffusion resistance. (2) The honeycomb ceramic catalyst for hydrogen production from natural gas water reforming of the present invention has a porous coating structure that improves the utilization rate of active components, can quickly start the hydrogen production reaction from natural gas water reforming, improve the hydrogen production efficiency, and achieves a methane conversion rate of over 75% at 650°C. (3) The honeycomb ceramic catalyst for hydrogen production from natural gas water reforming of the present invention has good mechanical strength and thermal stability in an integral honeycomb structure, and can operate stably for a long time in the high temperature and high pressure SOFC working environment; (4) The honeycomb ceramic catalyst for hydrogen production from natural gas water reforming of the present invention is easy to integrate and install, and can be customized according to the needs of SOFC, thereby improving the flexibility and adaptability of the system; (5) The method for preparing the honeycomb ceramic catalyst for hydrogen production by natural gas water reforming of the present invention adopts the top-feed vacuum coating method to make the active components of the catalyst evenly distributed, avoiding the problems of local hot spots and uneven reaction, and improving the stability and reliability of the reaction. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of the structure of the honeycomb ceramic catalyst for hydrogen production from natural gas water reforming according to the present invention; Figure 2 This is a schematic diagram of the top-feed vacuum coating method in the preparation method of the present invention; Figure 3 This is a flowchart illustrating the application of the honeycomb ceramic catalyst of the present invention in the catalytic reforming of natural gas into hydrogen. Detailed Implementation

[0022] The principles and features of the present invention are described below. The examples given are only for explaining the present invention and are not intended to limit the scope of the present invention.

[0023] like Figure 1 As shown, the natural gas-water reforming hydrogen production honeycomb ceramic catalyst of the present invention includes an ultra-high porosity honeycomb ceramic support and a composite active catalyst layer coated on the pore walls of the ultra-high porosity honeycomb ceramic support. The ultra-high porosity honeycomb ceramic support has a mesh size of 10,000-40,000 mesh. The composite active catalyst layer includes a metal active component, modified alumina and an additive, wherein the additive is cerium zirconium oxide.

[0024] The honeycomb ceramic catalyst for hydrogen production from natural gas-water reforming of this invention employs an ultra-high pore density honeycomb ceramic support, giving the catalyst high catalytic activity. The honeycomb structure reduces gas diffusion resistance, and the porous coating improves the utilization rate of active components, enabling rapid initiation of the natural gas-water reforming hydrogen production reaction and improving hydrogen production efficiency. The methane conversion rate reaches over 75% at 650℃. The integral honeycomb structure possesses excellent mechanical strength and thermal stability, allowing for long-term stable operation under high temperature and high pressure SOFC conditions. It is easy to integrate and install, and can be customized according to SOFC requirements, improving the system's flexibility and adaptability.

[0025] CeO2-ZrO2 composite oxides enhance resistance to carbon buildup and sintering, and the monolithic catalyst structure is wear-resistant, corrosion-resistant, and has a long service life.

[0026] Preferably, the active metal component is nickel. Using nickel as the active metal component has the triple advantages of high activity, low cost, and high temperature compatibility. In SOFC systems, it can overcome carbon deposition and sintering problems by being loaded onto a honeycomb ceramic carrier, achieving deep integration with the fuel cell stack and driving system efficiency improvement of more than 30%.

[0027] Preferably, the modified alumina is alumina with an increased specific surface area, having a specific surface area of ​​200-400 m². 2 / g; Compared to conventional alumina, the modified alumina used in this invention can increase its resistance to thermal aging.

[0028] The method for preparing the honeycomb ceramic catalyst for hydrogen production from natural gas water reforming of the present invention includes the following steps: S1. Prepare the honeycomb ceramic carrier raw material into the ultra-high porosity honeycomb ceramic carrier.

[0029] Preferably, the raw materials of the cellular ceramic carrier include inorganic solid components, organic components and water. The inorganic solid components include kaolin, spherical alumina and talc, and the organic components include methylcellulose, polyethyleneimine and molding release agent.

[0030] Preferably, in the inorganic solid component, the mass percentage of kaolin is 30.2%, the mass percentage of spherical alumina is 24.4%, and the mass percentage of talc is 45.4%; the average particle size of the spherical alumina is less than 1 μm.

[0031] Preferably, based on the mass of inorganic solid raw materials (100%), the mass fraction of methylcellulose is 3-6%, the mass fraction of polyethyleneimine is 0.25-0.75%, and the mass fraction of molding release agent is 1-3%.

[0032] S2. Prepare catalyst slurry for composite active catalyst layer.

[0033] Preferably, nickel nitrate is dissolved in water, and then modified alumina and cerium-zirconium composite are added and mixed evenly to obtain a catalyst slurry.

[0034] Preferably, in the catalyst slurry, the mass percentage of nickel nitrate is 25%; the mass percentage of modified alumina is 65%; and the mass percentage of cerium-zirconium composite is 10%.

[0035] S3. The catalyst slurry is coated onto the pore walls of the ultra-high porosity honeycomb ceramic carrier using the top-feed vacuum coating method.

[0036] The top-feed vacuum coating method involves precisely spraying a set weight of catalyst slurry from the top of the ultra-high porosity honeycomb ceramic carrier according to the target loading rate. A vacuum pump is then activated to evacuate the carrier pores (-0.03~-0.05 MPa). Under negative pressure, the slurry uniformly fills and adheres to the inner wall of the pores from top to bottom, achieving full coverage. Clean compressed air is then introduced to purge under positive pressure, removing excess slurry from the pores to prevent clogging and ensure a uniform coating.

[0037] The above method can make the active components of the catalyst evenly distributed, and the pores are not easily blocked, avoiding the problems of local hot spots and uneven reaction, thus improving the stability and reliability of the reaction. In addition, the injection of a quantitative slurry during the coating process enables controllable loading rate.

[0038] S4. Dry and calcine to obtain a honeycomb ceramic catalyst.

[0039] The honeycomb ceramic catalyst of this invention can be applied to the hydrogen production reaction of natural gas-water reforming in SOFCs, specifically at a temperature of 650°C and a space velocity of 5000-20000 h⁻¹. -1 Under operating conditions with a water-to-carbon ratio of 3, the aforementioned honeycomb ceramic catalyst is used to catalyze the mixture of natural gas and water.

[0040] like Figure 3 As shown, after natural gas (methane) and water react in a mixer, they enter a honeycomb ceramic catalyst and undergo the following reaction: The products after the reaction are passed through a condenser and a dryer in sequence to obtain hydrogen, carbon dioxide and carbon monoxide.

[0041] The honeycomb ceramic catalyst of the present invention can effectively improve hydrogen production efficiency, with a methane conversion rate of over 75% at 650°C.

[0042] The monolithic structure of the honeycomb ceramic catalyst of the present invention facilitates installation and integration, reduces system complexity and cost, and improves system reliability and stability; it can also effectively inhibit carbon deposition and extend the service life of the catalyst.

[0043] The present invention will be illustrated by specific embodiments below.

[0044] Example 1 Preparation of ceramic carriers: First, 30.2% kaolin, 24.4% spherical alumina (less than 1 μm by mass), and 45.4% talc are thoroughly mixed using a mixing device. Then, water, methylcellulose, polyethyleneimine, molding release agent, etc. are added and thoroughly mixed. After vacuum kneading, clay segments with suitable softness and hardness are formed. The clay segments are then extruded into a honeycomb structure, microwave dried, and fired in an automatic kiln to obtain 10,000 mesh, 20,000 mesh, and 40,000 mesh ultra-high porosity honeycomb ceramic carriers.

[0045] Catalyst preparation: 25% nickel nitrate (by mass) was dissolved in water, and 65% modified alumina and 10% cerium-zirconium composite were added. After thorough mixing, a homogeneous solution with a solid content of 20% was obtained. A top-feed vacuum coating method was used to quantitatively fill the slurry into a slurry tank. The slurry was then sprayed from the top surface of the honeycomb ceramic using a nozzle. Compressed air was then used to suction the slurry from the bottom surface to evenly coat the inner walls of the pores of the carrier and remove excess slurry from the pores. After coating, the slurry was dried and calcined to obtain the finished honeycomb catalyst.

[0046] Using a 10,000-mesh honeycomb ceramic catalyst, at a temperature of 650℃ and a space velocity (GHSV) of 5000 h⁻¹, -1 An integrated SOFC experiment was conducted under operating conditions with a water-to-carbon ratio of 3. After stable operation, the methane conversion rate was measured. Examples 2-4 are all based on Example 1, the difference being the different gas space velocities used in the SOFC integration performance test.

[0047] The test parameters and performance evaluation indicators for Examples 1-4 are shown in Table 1: Table 1. Test parameters and performance evaluation indicators for Examples 1-4 Examples 5-9 are the same as Examples 1-4, except that the honeycomb ceramic catalyst used in the SOFC experiment is 20,000 mesh.

[0048] The test parameters and performance evaluation indicators for specific embodiments 5-8 are shown in Table 2: Table 2 Test parameters and performance evaluation indicators for Examples 5-8 Examples 9-12 are the same as Examples 1-4, except that the honeycomb ceramic catalyst used in the SOFC experiment is 40,000 mesh.

[0049] The test parameters and performance indicators for specific embodiments 9-12 are shown in Table 3: Table 3 Test parameters and performance indicators for Examples 9-12 Comparative Example 1 Referring to Example 1, the difference is that the catalyst used in the SOFC experiment is a single Ni component.

[0050] Comparative Example 2 Referring to Example 1, the difference lies in the fact that the catalyst used in the SOFC experiment has a mass percentage of 25% nickel nitrate, a mass percentage of 60% modified alumina, and a mass percentage of 15% cerium-zirconium composite.

[0051] Comparative Example 3 Referring to Example 1, the difference lies in the fact that the catalyst used in the SOFC experiment has a mass percentage of 25% nickel nitrate, a mass percentage of 70% modified alumina, and a mass percentage of 5% cerium-zirconium composite.

[0052] Comparative Example 4 Referring to Example 1, the difference lies in the fact that the catalyst used in the SOFC experiment has a mass percentage of 25% nickel nitrate, a mass percentage of 65% modified alumina, and a mass percentage of 10% cerium dioxide.

[0053] Comparative Example 5 Referring to Example 1, the difference is that the monolithic honeycomb ceramic catalyst used in the SOFC experiment is 1000 mesh, and it is currently impossible to prepare honeycomb ceramic supports with higher pore density (>40000 mesh).

[0054] Comparative Example 6 Referring to Example 1, the difference lies in that the monolithic honeycomb ceramic catalyst used in the SOFC experiment was prepared by impregnation. After impregnation, the loading was low and the coating was uneven.

[0055] In addition, since the highest mesh count of silicon carbide honeycomb ceramics is currently 600 cpsi, silicon carbide honeycomb ceramics cannot be used as a carrier for high mesh counts, making comparative testing impossible.

[0056] The test parameters and performance indicators of Comparative Examples 1-6 are shown in Table 4: Table 4 Test parameters and performance indicators for Comparative Examples 1-6 The comparison between Examples 1-12 and Comparative Examples 1-6 shows that the pore density of the cellular ceramic carrier, the synergistic effect of the catalyst components, and the coating process jointly determine the SOFC methane reforming coupled power generation performance.

[0057] Under constant temperature of 650℃ and water-to-carbon ratio of 3, as the space velocity increases from 5000 h⁻¹... -1 Increased to 20,000 h -1The methane conversion rates of Examples 1-4 (10,000 mesh), Examples 5-8 (20,000 mesh), and Examples 9-12 (40,000 mesh) increased from 75.26%, 76.32%, and 77.69% to 83.73%, 83.98%, and 84.5%, respectively, with the output power density also increasing synchronously from 0.52, 0.54, and 0.56 W / cm³. 2 Increased to 0.65, 0.67, and 0.71 W / cm² 2 The results show that high air velocity enhances mass transfer and promotes the reaction, and the higher the pore density, the more significant the gain.

[0058] 40,000 mesh carrier at 20,000 h -1 The highest methane conversion rate of 84.5% and power density of 0.71 W / cm³ were achieved at the specified space velocity. 2 This demonstrates that 10,000-40,000 mesh ultra-high pore density honeycomb ceramics can break through the mesh limit of traditional 600 cpsi silicon carbide supports, providing more active sites and shorter diffusion paths for the reaction.

[0059] Regarding the catalyst, Comparative Example 1, with Ni as the single component, showed a methane conversion of only 56.3% and a power density of 0.39 W / cm³. 2 This is significantly lower than the 75.26% and 0.52 W / cm² of Example 1. 2 This indicates that the acidic-oxygen storage bifunctional interface constructed by modified alumina and cerium-zirconium composite oxide is indispensable; Comparative Example 2 (cerium-zirconium increased to 15%), Comparative Example 3 (cerium-zirconium reduced to 5%), and Comparative Example 4 (cerium dioxide used alone) yielded methane conversion rates of 70.2%, 73.1%, and 72.9%, respectively, and a yield of 0.48 W / cm³. 2 0.51 W / cm 2 0.5 W / cm 2 The power densities of all samples were lower than those of the 10% cerium-zirconium ratio in Example 1, indicating that an appropriate amount of cerium-zirconium can optimize oxygen migration and Ni dispersion, while excessive or insufficient amounts weaken the synergy.

[0060] Comparative Example 5, using a 1000-mesh low-porosity support, yielded only a 64.5% methane conversion and 0.45 W / cm³. 2 This further confirms that insufficient pore density limits the active area and mass transfer efficiency.

[0061] Comparative Example 6, using the impregnation method, achieved only a 63.7% methane conversion rate and 0.34 W / cm³ due to low loading and uneven coating. 2 The results are far lower than those of Example 1, which uses a vacuum coating method, demonstrating that a uniform, quantitative, and controllable vacuum coating-suction process is key to ensuring uniform active layer thickness and avoiding pore blockage.

[0062] In summary, the 40,000-mesh ultra-high porosity honeycomb ceramic carrier, the Ni-modified alumina-10% cerium-zirconium composite oxide multi-element catalyst, and the vacuum coating-suction integrated process constitute the optimal technical route for SOFC integrated reforming power generation that balances high methane conversion rate and output power density and is adaptable to high space speed operation.

[0063] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A honeycomb ceramic catalyst for hydrogen production via natural gas-water reforming, characterized in that, It includes an ultra-high porosity honeycomb ceramic carrier and a composite active catalyst layer coated on the pore walls of the ultra-high porosity honeycomb ceramic carrier. The ultra-high porosity honeycomb ceramic carrier has a mesh size of 10,000-40,000 mesh. The composite active catalyst layer includes a metal active component, modified alumina, and cerium zirconium oxide.

2. The honeycomb ceramic catalyst for hydrogen production from natural gas water reforming according to claim 1, characterized in that, The active metallic component is nickel.

3. A method for preparing a honeycomb ceramic catalyst for hydrogen production from natural gas water reforming as described in claim 1 or 2, characterized in that, Includes the following steps: S1. Prepare the honeycomb ceramic carrier raw material into the ultra-high porosity honeycomb ceramic carrier; S2. Prepare the catalyst slurry for the composite active catalyst layer; S3. The catalyst slurry is coated onto the pore walls of the ultra-high porosity honeycomb ceramic carrier using a top-feed vacuum coating method. S4. Dry and calcine to obtain the honeycomb ceramic catalyst.

4. The method for preparing a honeycomb ceramic catalyst for hydrogen production from natural gas water reforming according to claim 3, characterized in that, The raw materials of the cellular ceramic carrier include inorganic solid components, organic components and water. The inorganic solid components include kaolin, spherical alumina and talc, and the organic components include methylcellulose, polyethyleneimine and molding release agent.

5. The method for preparing a honeycomb ceramic catalyst for hydrogen production from natural gas water reforming according to claim 4, characterized in that, In the inorganic solid component, the mass percentage of kaolin is 30.2%, the mass percentage of spherical alumina is 24.4%, and the mass percentage of talc is 45.4%; the average particle size of the spherical alumina is less than 1 μm.

6. The method for preparing a honeycomb ceramic catalyst for hydrogen production from natural gas water reforming according to claim 4, characterized in that, Based on the inorganic solid raw material mass of 100%, the mass fraction of methylcellulose is 3-6%, the mass fraction of polyethyleneimine is 0.25-0.75%, and the mass fraction of molding release agent is 1-3%.

7. The method for preparing a honeycomb ceramic catalyst for hydrogen production from natural gas water reforming according to claim 3, characterized in that, In step S2, the catalyst slurry is prepared by dissolving nickel nitrate in water, then adding modified alumina and cerium-zirconium composite, and mixing them evenly to obtain the catalyst slurry.

8. The method for preparing a honeycomb ceramic catalyst for hydrogen production from natural gas water reforming according to claim 7, characterized in that, In the catalyst slurry, based on the mass of inorganic solid raw materials as 100%, the mass percentage of nickel nitrate is 25%; the mass percentage of modified alumina is 65%; and the mass percentage of cerium-zirconium composite is 10%.

9. The method for preparing a honeycomb ceramic catalyst for hydrogen production from natural gas water reforming according to claim 3, characterized in that, In step S3, the upper feeding vacuum coating method involves spraying the catalyst slurry onto one end face of the ultra-high porosity honeycomb ceramic carrier, and then suctioning it from the other end face of the ultra-high porosity honeycomb ceramic carrier using compressed air at a pressure of -0.03 to -0.05 MPa.

10. The application of a honeycomb ceramic catalyst as described in claim 1 or 2 in the natural gas-water reforming hydrogen production reaction of SOFC, characterized in that, At normal pressure, at a temperature of 650℃, the space velocity is 5000-20000 h⁻¹. -1 Under operating conditions with a water-to-carbon ratio of 3, the aforementioned honeycomb ceramic catalyst is used to catalyze the mixture of natural gas and water.